PENGEMBANGAN KECERDASAN MUSIKAL MELALUI KEGIATAN TEBAK LAGU BERBASIS INSTRUMEN UNTUK ANAK USIA 5 – 6 TAHUN - Tiara sari; Hanum Maulidah; Siti Esma Sari; Sri Indriani Harianja (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research examines the development of musical intelligence through song guessing activities based on the piano instrument for children aged 5-6 years. Through a comprehensive literature study, this research analyzes various aspects of children's development that can be stimulated through interactive musical activities. The research results show that instrument-based song guessing activities have significant potential in improving children's auditory abilities, musical memory, social skills, creativity, music-language connections and emotional awareness. This study also underscores the importance of post-activity discussions in strengthening children's musical understanding. Based on literature findings, a design for song guessing activities using pianists in small groups is proposed as a practical method for developing musical intelligence of children aged 5-6 years